2020
DOI: 10.1089/can.2019.0048
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Average Cannabis Use in Relation to Hypertriglyceridemic Waist Phenotype in U.S. Adults: A Population-Based Cross-Sectional Study

Abstract: Background and Aims: With a growing number of states legalizing recreational or medical cannabis, prevalence of cannabis users is expected to markedly increase in the future. We aim to determine the association between lifetime cannabis use and the likelihood for hypertriglyceridemic waist (HTGW + /+) phenotype in U.S. adults. Methods: We abstracted data from the National Health and Nutrition Examination Survey from 2009 to 2016. We estimated the minimal lifetime cannabis use using the duration of regular expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…For instance, Ngueta et al, among Inuit adults, found an OR of 0.56 for obesity (BMI ≥ 30 kg/m 2 ) for past-year cannabis use as compared to non-users (Ngueta et al 2015 ). They also found a similar association between frequent cannabis use (but not former nor infrequent use) and concurrent elevated triglycerides and waist circumference (Ngueta 2020 ). However, causal association was not found in a recent Mendelian randomization study (Alayash et al 2021 ).…”
Section: Discussionmentioning
confidence: 74%
“…For instance, Ngueta et al, among Inuit adults, found an OR of 0.56 for obesity (BMI ≥ 30 kg/m 2 ) for past-year cannabis use as compared to non-users (Ngueta et al 2015 ). They also found a similar association between frequent cannabis use (but not former nor infrequent use) and concurrent elevated triglycerides and waist circumference (Ngueta 2020 ). However, causal association was not found in a recent Mendelian randomization study (Alayash et al 2021 ).…”
Section: Discussionmentioning
confidence: 74%